1983
DOI: 10.1007/bf00965104
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes of rat brain membranes with aging

Abstract: Modification of membrane composition and enzymatic activities both in total brain homogenate and purified synaptic plasma membrane of 3 and 24 month old rats has been investigated. Protein, cholesterol and phospholipid content and (Na+, K+)ATPase and 2',3' cyclic nucleotide phosphohydrolase activities were determined. The major changes occurred in the whole homogenate where a general increase in total protein and cholesterol content with age and a significant increase of the cholesterol/phospholipids molar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 24 publications
2
23
2
Order By: Relevance
“…These results are in agreement with others (Samson and Quinn 1967;Mishra and Shankar 1980;Tsutsumi et al 1995) showing enhanced Na,K-ATPase activity with age. These findings of increased SPM Na,K-ATPase activity with age differ from those reported by Calderini et al (1983) who showed a decrease ( 35%) in SPM Na,K-ATPase with age. The reason for this discrepancy between studies may be due to the time periods in which Na,K-ATPase activity was measured (weeks vs. months).…”
Section: Discussioncontrasting
confidence: 99%
“…These results are in agreement with others (Samson and Quinn 1967;Mishra and Shankar 1980;Tsutsumi et al 1995) showing enhanced Na,K-ATPase activity with age. These findings of increased SPM Na,K-ATPase activity with age differ from those reported by Calderini et al (1983) who showed a decrease ( 35%) in SPM Na,K-ATPase with age. The reason for this discrepancy between studies may be due to the time periods in which Na,K-ATPase activity was measured (weeks vs. months).…”
Section: Discussioncontrasting
confidence: 99%
“…Like tCho, phosphorylethanolamine levels continued their developmental trend for decrease during adulthood and aging. The inverse trajectory in the evolution of tCho and phosphorylethanolamine levels in the aging brain may be related to modifications in cell membrane fluidity (Calderini et al, 1983). In line with this, a 31 P MRS study showed that the glycerylated forms of such phospholipids increase with age in the human brain (Blüml et al, 1999).…”
Section: Discussionmentioning
confidence: 73%
“…A number of reports have indicated that aging is associated with changes in membrane composition (15,42,43), and, although the underlying cause remains unclear, it has been accepted that lipid peroxidation, apparently triggered by reactive oxygen species, can lead to a decrease in membrane polyunsaturated fatty acids (23), which contributes to membrane rigidity (22,44). We have found that lipid peroxidation is increased, whereas membrane arachidonic acid concentration is decreased, in hippocampal tissue prepared from aged rats 2 ; these data, albeit obtained in separate experiments, suggested that arachidonic acid may be one target molecule for lipid peroxidation.…”
Section: Fig 3 the Age-related Increases In Il-1␤ Concentration (A)mentioning
confidence: 99%
“…Previous observations have indicated changes in membrane composition, particularly in arachidonic acid concentration, with age (3,19,42,43). Arachidonic acid modulates synaptic function (3,5), and its membrane concentration correlates with ability of aged rats to sustain LTP (3); therefore, it was predicted that the age-related changes in arachidonic acid may underlie some of the impairments in neuronal function that accompany aging (e.g.…”
Section: Fig 3 the Age-related Increases In Il-1␤ Concentration (A)mentioning
confidence: 99%